“I AM TOTALLY ISOLATED”: EXPERIENCES OF ADULTS WITH ACQUIRED PHYSICAL DISABILITIES DURING COVID-19 PANDEMIC LOCKDOWN IN SOUTH AFRICA - Muller-Kluits, Noreth; Slabbert, Ilze (Social Work/Maatskaplike Werk, 2023)
The sudden onset of the COVID-19 pandemic impacted various sectors, including social work services to persons with physical disabilities. This qualitative study focused on the experiences of adults with an acquired physical disability who needed social work support. To understand these experiences, an ecological perspective was utilised as a theoretical basis. The study was conducted during the COVID-19 pandemic lockdown experienced internationally, including in South Africa. The impact of the COVID-19 pandemic was found to be challenging for persons with disabilities, specifically in terms of isolation, lack of resources and economic distress. Recommendations for future interventions to address the social needs of adults with a physical disability in disaster situations such as COVID-19 are also presented.